Absorbed doses in salivary and thyroid glands from panoramic radiography and cone beam computed tomography - Heiden,Katia Regina (2018)
Abstract Introduction: Panoramic radiography and cone beam computed tomography (CBCT) are very important in the diagnosis of oral diseases, however patients are exposed to the risk of ionizing radiation. This paper describes our study aimed at comparing absorbed doses in the salivary glands and thyroid due to panoramic radiography and CBCT and estimating radiation induced cancer risk associated with those methods. Methods Absorbed doses of two CBCT equipment (i-CAT® Next Generation and SCANORA® 3D) and a digital panoramic device (ORTHOPANTOMOGRAPH® OP200D) were measured using thermoluminescent dosimeters loaded in an anthropomorphic phantom on sublingual, submandibular, parotid and thyroid glands. Results Absorbed doses in the i-CAT® device ranged between 0.02 (+/-0.01) and 2.23 mGy (+/-0.03), in the SCANORA™ device ranged from 0.01 (+/-0.01) to 2.96 mGy (+/-0.29) and in the ORTHOPANTOMOGRAPH® OP200D ranged between 0.04 mGy and 0.78 mGy. The radiation induced cancer risk was highlighted in the salivary glands, which received higher doses. The protocols that offer the highest risk of cancer are the high resolution protocols of CBCT equipment. Conclusion CBCT exposes patients to higher levels of radiation than panoramic radiography, so the risks and benefits of each method should be considered. The doses in CBCT were dependent on equipment and exposure parameters, therefore adequate selection minimizes the radiation dose.